2010
DOI: 10.1590/s1677-04202010000300007
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in fatty acid composition due to cold exposure at the vegetative stage in rice

Abstract: Rice is a tropical plant, so cold temperature may be detrimental to its development, depending on the genotype and environmental conditions. Degree of lipid unsaturation has been related to cold tolerance due to its effect on membrane stability. So, the aim of this study was to characterize the fatty acid composition and its alterations due to cold temperature in rice genotypes of diversified origin. Forty-four rice genotypes at the V 4 stage were submitted to two temperature conditions: 10°C and 28°C for two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 17 publications
2
19
0
Order By: Relevance
“…In contrast, in cold tolerant genotypes, unsaturated fatty acids showed a rise, and saturated acids undergone a reduction. (Cruz et al, 2010). This may interpret the role of lipid unsaturation in the maintenance of cell membrane stability and then cold tolerance.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, in cold tolerant genotypes, unsaturated fatty acids showed a rise, and saturated acids undergone a reduction. (Cruz et al, 2010). This may interpret the role of lipid unsaturation in the maintenance of cell membrane stability and then cold tolerance.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, OsFAD8 has a functional role in maintaining levels of trienoic fatty acids and stress tolerance at low temperatures in rice [5]. In one study [6], linolenic acid levels increased and palmitic acid levels decreased in cold tolerant rice genotypes exposed to chilling; the opposite behavior was observed in cold sensitive genotypes. Transcriptional regulation is the core component of the complex genetic network associated with plant responses to cold.…”
Section: Introductionmentioning
confidence: 99%
“…Differences in the content of saturated and unsaturated fatty acids were observed among plants at the vegetative stage from tolerant and sensitive genotypes only after cold exposure (da Cruz et al. ). The same authors found that among the most abundant types of fatty acids, levels of linolenic acid increased in the tolerant genotypes and of palmitic acid decreased in these same genotypes, confirming an important role for the unsaturated fatty acids in maintaining membrane stability during cold stress.…”
Section: Tools To Evaluate Cold Stress In Ricementioning
confidence: 99%